Analysis of the Mechanism for Handling Problem Financing in the Status of Sharia Mortgage Collectability using the Restructuring Method - Sandi, Muhammad; Inayah, Nurul; Anggraini, Tuti (Electronic Journal of Education, Social Economics and Technology, 2025)
In this research, the restructuring method was used at Bank Sumut Syariah KCP Kota Baru to see how the collectability status of Sharia Home Ownership Credit (KPR) handled problematic financing. Non-Performing Financing (NPF) is an important issue in the sharia banking industry, including sharia mortgage financing products. This research uses a qualitative study with a case study approach. Data was collected through interviews and observations. The research results show that Bank Sumut Syariah KCP Kota Baru implemented several strategies in handling problematic financing for Sharia KPR by rescheduling or rescheduling. By implementing a comprehensive handling mechanism, Bank Sumut Syariah KCP Kota Baru seeks to minimize financing risks. It is hoped that this research will provide theoretical and practical contributions to the progress of the sharia banking industry, especially in dealing with the risk of problematic financing in sharia housing credit (KPR) products.